Pengaruh Efek Iatrogenik Dalam Perawatan Ortodonti - Tuti Alawiyah (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Nowadays, orthodontic treatment is a very common kind of treatment in modern society. The demand of orthodontic treatment is still high not only within growing or young patients but also within adult patients especially in urban area. But orthodontist has to remember that there is an effect that they have to avoid or anticipate related to its treatement. Purpose: The aims of this study to review iatrogenic effect in contemporary orthodontic treatment. Literature review: This iatrogenic effect is very destructive to hard and soft tissue in the mouth. The destruction includes to the tooth, gingiva, and supportive tissue inside the mouth. The effect could damage the root tissue aswell. The most common phenomenon is theenamel decalsification which is the destruction of enamel tissue because of inadequate plaque control. Conclusion: In every visit to orthodontist for appliance check up, the orthodontist should never forget to do appropiate cleaning. Inside the paper, the topic will be dicussed more deeply.